Safety of 3‐fucosyllactose (3‐FL) produced by a derivative strain of Escherichia coli K‐12 DH1 as a novel food pursuant to Regulation (EU) 2015/2283 - EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA); Dominique Turck; Torsten Bohn; Jacqueline Castenmiller; Stefaan De Henauw; Karen Ildico Hirsch‐Ernst; Alexandre Maciuk; Inge Mangelsdorf; Harry J. McArdle; Androniki Naska; Carmen Pelaez; Kristina Pentieva; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on 3‐fucosyllactose (3‐FL) as a novel food (NF) pursuant to Regulation (EU) 2015/2283. The NF is mainly composed of the human‐identical milk oligosaccharide (HiMO) 3‐FL, but it also contains d‐lactose, l‐fucose, 3‐fucosyllactulose and a small fraction of other related saccharides. The NF is produced by fermentation by a genetically modified strain (Escherichia coli K‐12 DH1 MDO MAP1834) of E. coli K‐12 DH1 (DSM 4235). The information provided on the manufacturing process, composition and specifications of the NF does not raise safety concerns. The applicant intends to add the NF to a variety of foods, including infant formula and follow‐on formula, food for special medical purposes and food supplements (FS). The target population is the general population. The anticipated daily intake of 3‐FL from both proposed and combined (authorised and proposed) uses at their respective maximum use levels in all population categories does not exceed the highest intake level of 3‐FL from human milk in infants on a body weight basis. The intake of 3‐FL in breastfed infants on a body weight basis is expected to be safe also for other population groups. The intake of other carbohydrate‐type compounds structurally related to 3‐FL is also considered of no safety concern. FS are not intended to be used if other foods with added 3‐FL or human milk are consumed on the same day. The Panel concludes that the NF is safe under the proposed conditions of use.